COVID-19’s Vaccine Rejection: Lesson Learned To Preserving Health Security In Indonesia - Reinpal Falefi; Hikmat Zakky Almubaraq; Susilawati Susilawati (Interest : Jurnal Ilmu Kesehatan, 2022)
Background: Indonesia is a country with low COVID-19 vaccination coverage from 2020 through 2021. Different sociodemographic conditions determine the success of vaccination in suppressing the transmission of COVID-19. This systematic review aims to identify the reasons for the refusal of the COVID-19 vaccine among the general and vulnerable communities in Indonesia. Methods: This study uses a systematic review method using PubMed and Google Scholar. The keywords used are COVID-19 vaccine, acceptance, determinant, and Indonesia. The article, which was specifically researched, presents the acceptance of the COVID-19 vaccine in Indonesia only in 2020 and 2021. Elicit information from found articles to form conclusions for each article. Results: Based on 12 studies, the main causes of the rejection of the COVID-19 vaccine in Indonesia are knowledge and negative attitudes. In the aspect of knowledge, three things become problems, namely fear of the side effects of vaccination, doubts about the effectiveness of vaccines, and doubts about vaccine safety. Negative attitudes are influenced by propaganda and conspiracies. Conclusion: The general population and vulnerable people in Indonesia are more likely to reject the COVID-19 vaccine, so the target for mass vaccination is not achieved, the main reasons being knowledge and perception. Control strategies and invitations for specific COVID-19 vaccinations are critical in order to get the general public and vulnerable populations to participate in vaccination activities.